The lionfishes: Comparative development of Pterois volitans, Dendrochirus barberi, and D. hemprichi (Scorpaeniformes: Scorpaenidae: Pteroinae) and discrimination of their early life stages from non-pteroine scorpaenid genera in the Western North Atlantic - Ditty, James G.; Malca, Estrella; Vásquez-Yeomans, Lourdes (Zootaxa, 2024)
Despite the threat that lionfishes pose to non-native marine ecosystems worldwide, their early life stages (ELS) remain difficult to distinguish from morphologically similar taxa due to inadequate descriptions and poorly defined taxonomic characters. Two members of the Indo-Pacific marine assemblage commonly known as lionfishes, zebrafishes, firefishes, turkeyfishes, and butterfly-cods (Scorpaeniformes: Scorpaenidae: Pteroinae) are invasive in the Western North Atlantic (WNA). Here, we describe the ELS of Pterois volitans, Dendrochirus barberi, and two transforming larvae and an early juvenile of D. hemprichi; review the early development of D. zebra and a larva described as D. bellus; identify characteristics that distinguish P. volitans from the four members of Dendrochirus; and compile meristic and distribution data for all currently valid species of lionfishes worldwide based on recent revisions and updated nomenclature. We also briefly describe a small juvenile of two poorly known non-pteroine deep-water scorpaenids, and discuss characteristics that distinguish the five pteroines from non-pteroine scorpaenid genera in the WNA. Differences in relative length and elevation of the parietal and nuchal spines, and in pigmentation patterns distinguish P. volitans from the four members of Dendrochirus. Pterois volitans has parietal spines two or more times longer than the nuchals with both sets of spines oriented about 30° above the longitudinal axis of the head, whereas the four members of Dendrochirus have relatively short parietal and nuchal spines subequal in length that lay flatter against the cranium (i.e., elevation ≤15° above longitudinal axis of head). Transforming larvae of the four members of Dendrochirus also develop saddles of pigment along the dorsal and ventral margins of the body that P. volitans lacks at the sizes examined. One or more of the following suite of traits distinguish larvae of the five pteroines from those of non-pteroine scorpaenids and other morphologically similar taxa: the presence or absence of a “shield” of pigment over the dorsolateral margin of the visceral mass (may be reduced or augmented with scattered blotches of pigment in larger larvae of some taxa); the relative length, elevation, and placement of the parietal and nuchal spines; the presence or absence of a small slit behind the fourth gill arch; differences in pectoral-fin length, shape, and extent of pigmentation; the relative size, length, and placement of spines along the posterior shelf of the preopercle (PPO); and the presence or absence, number, and placement of spine(s) along the opercle.